George and Martha back in town - Marshall, James, 1942-1992. (Boston : Houghton Mifflin, 1984)
Though their friendship is often tested, George and Martha survive with a sense of humor.
Keywords: Children's stories, American; Friendship -- Fiction; Hippopotamus -- Fiction